2014
DOI: 10.1117/12.2046296
|View full text |Cite
|
Sign up to set email alerts
|

Extending the scope of poly(styrene)-block-poly(methyl methacrylate) for directed self-assembly

Abstract: Directed self-assembly (DSA) is a promising technique for extending conventional lithographic techniques by being able to print features with critical dimensions under 10 nm. The most widely studied block copolymer system is polystyreneblock-polymethyl methacrylate (PS-b-PMMA). The system is well understood in terms of its synthesis, properties and performance in DSA. However, PS-b-PMMA also has a number of limitations that impact on its performance and hence scope of application. The primary limitation is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Apparently, the first use of an IL to process a BCP materials was Bennett et al, where it was shown that adding a small amount of IL such as 1-ethyl-3-methylimidazolium bis­(trifluoromethane sulfonyl)­amide (EMIM NTf 2 ) can enhance χ parameter, studied from the domain swelling of the PS-PMMA revealed by small-angle X-ray scattering (SAXS) ( L o ∼ χ 1/6 ), and enable order in a low N system that would not otherwise order. , Moreover, they also found that ILs can induce morphological transition in hexagonally ordered cylindrical films to lamellar morphology when used in excess due to domain swelling of the minority cylinder-forming block. More recently, Chen et al have demonstrated a similar effects in a low M w BCP material to attain nanopattern pitches below 20 nm .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Apparently, the first use of an IL to process a BCP materials was Bennett et al, where it was shown that adding a small amount of IL such as 1-ethyl-3-methylimidazolium bis­(trifluoromethane sulfonyl)­amide (EMIM NTf 2 ) can enhance χ parameter, studied from the domain swelling of the PS-PMMA revealed by small-angle X-ray scattering (SAXS) ( L o ∼ χ 1/6 ), and enable order in a low N system that would not otherwise order. , Moreover, they also found that ILs can induce morphological transition in hexagonally ordered cylindrical films to lamellar morphology when used in excess due to domain swelling of the minority cylinder-forming block. More recently, Chen et al have demonstrated a similar effects in a low M w BCP material to attain nanopattern pitches below 20 nm .…”
Section: Introductionmentioning
confidence: 72%
“…24 Interestingly, they have also been shown to increase the Flory−Huggins interaction parameter, χ, in BCPs, thereby enabling ordering in low N BCP systems with smaller feature size. 24,25 Apparently, the first use of an IL to process a BCP materials was Bennett et al, where it was shown that adding a small amount of IL such as 1-ethyl-3-methylimidazolium bis-(trifluoromethane sulfonyl)amide (EMIM NTf 2 ) can enhance χ parameter, studied from the domain swelling of the PS-PMMA revealed by small-angle X-ray scattering (SAXS) (L o ∼ χ 1/6 ), and enable order in a low N system that would not otherwise order. 24,25 Moreover, they also found that ILs can induce morphological transition in hexagonally ordered cylindrical films to lamellar morphology when used in excess due to domain swelling of the minority cylinder-forming block.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental phase diagrams can be used to predict these morphologies formations. The morphology of a copolymer can be influenced by solvents [10,11,12], composition [1,13,14,15], temperature [13,15,16,17,18], external forces [19,20], additives [17,21,22,23,24,25,26], etc. Morphology of copolymer can be useful for a broad range of applications.…”
Section: Introductionmentioning
confidence: 99%